A conceptual paper on the significant role of digital media in contemporary da’wah within the technological era / Usbah Yousaf, Nur Nasliza Arina Mohamad Nasir and Noor Nirwandy Mat Noordin - Yousaf, Usbah; Mohamad Nasir, Nur Nasliza Arina; Mat Noordin, Noor Nirwandy (Faculty of Communication & Media Studies, 2025)
The concept of Contemporary Da’wah involves using digital media as a means for preachers to convey and spread Da’wah messages to their audiences. In today's digital age, many preachers and content creators utilize social media platforms to share Da’wah, making it easier for them to communicate Islamic teachings to a wider audience. This study aims to explore the crucial role of digital media in contemporary Da’wah in the technological era. The research methodology is based on a review of secondary data, including reference materials from previous studies. These sources consist of books, papers, journal articles, newspapers, and credible online content that address topics related to: (1) Contemporary Da’wah, (2) Digital Media, and (3) the Technological Era. The analysis reveals that the advancement of technology serves its core purpose of fostering transformative changes, which extend to various aspects of human life, including Islamic Da’wah. The rise of digital media, supported by social media platforms, has expanded the ways in which Da’wah is spread beyond the traditional methods of preaching. Today, Da’wah can be efficiently shared through technology, overcoming geographical and physical barriers, reaching individuals across different locations, from one mobile device to another, from home to home, and even across international borders.